PEMANFAATAN MEDIA ARTIFICIAL INTELLEGENCE DALAM MENINGKAT-KAN LITERASI TERHADAP HASIL BELAJAR IPAS MATERI DI BUMI DAN KRISIS ENERGI PADA MURID KELAS IV MI AL-BUKHORI SURABAYA - Achmad Fajar Yusro; Suprihatien; Yudha Popiyanto Suprihatien (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the low literacy rates and suboptimal learning outcomes in Natural and Social Sciences (IPAS) among 6th-grade students at MI Al-Bukhori Surabaya, where average scores remained below the school's minimum mastery criteria (KKTP) of 79 due to low engagement and underutilized digital tools for academic learning. This research aims to evaluate the effectiveness of utilizing ChatGPT-based Artificial Intelligence (AI) media to improve literacy and learning outcomes regarding